Heart rate reserve versus talk test : is there a similar training effect? - Turek, Jillian N. (My University, 2016)
The Talk Test (TT) is a submaxirnal, incremental exercise test that is useful in prescribing exercise based on an individual's ability to speak comfortably during exercise. This study compared the training effects of two differentlO-week training intensities on endurance adaptions in sedentary, ymmg adults. Forty-four adults ventilatory threshold (VT) 1.59±0.39 Lmin-1 were randomized to two training groups. The training program was 10 weeks in duration (3 times weekly for 40 minutes per session). The Talk Test group (n=20) performed all 3D training sessions solely using the TT as the intensity control. Subjects rated their speech comfort every 5-minute stage after reciting a standardized paragraph. Speech comfort, heart rate (HR), and Rating of Perceived Exertion (RPE) were recorded every 5 min. The Heart Rate Reserve (HRR) group (n=24) performed at %HRR ranges 40-59% in week 1-4, 50-69% in week 5-8, and 60-79% in week 9-10. Heart rate and RPE were recorded every 5 min. Pre and post intervention, subjects were tested for maximal oxygen consumption (V02max) and VT. The results concluded that both groups improved from pre to post intervention (P<.05), but no significant differences were evident between groups (P>0.05). The TT may be used a simple and non-invasive method to prescribe exercise intensity compared to HRR. Given that maximal exercise tests to detect maximal heart rate (HRmax) are not widely available, the equivalent responses to training is available using the simpler TT method. The TT is an effective and attractive alternative to the %HRR method which has been the gold standard for exercise prescription.
Keywords: Kinesiology; Exercise--physiological aspects; Heart function tests